Psychosocial and Motor Characteristics of Patients With Hypermobility - Lamari, Mateus M.; Lamari, Neuseli M.; Araujo-Filho, Gerardo M.; Medeiros, Michael P.; Pugliesi Marques, Vitor R.; Pavarino, Érika C. (Frontiers in Psychiatry, 2022)
Objectives: To identify psychosocial and motor aspects among Brazilian of both genders with JH, to characterize JH using the Beighton's total score in function of gender and age; by "growing pain," to verify several manifestations. such as fatigue, attention deficit, anxiety, insomnia, sleepiness, apathy/quietness, depression, delayed ambulation, inability to crawl or difference in crawling technique, impaired spatial and/or temporal orientation, social isolation, and having been stigmatized as "lazy/clumsy/stubborn/quiet." Methods: This retrospective, observational, quantitative, and cross-sectional study used data obtained through analyses of descriptive and inferential crossings between 2012 and 2020 of 482 medical records of individuals between 1 and 76 years of age, from most Brazilian states. Analysis of JH using the method proposed by Beighton et al (1973) included determining the ability of a person. "Descriptive and inferential statistics were used. Results: In the complete sample, JH, predominant in the upper limbs, the majority were females, had a total Beighton score of ≥6, which decreased with increasing age. It was pointed differents psychosocial implications. Conclusion: JH was predominant in the upper limbs; most of whom were females, aged ≥15 years, with the Beighton total score of ≥6 in all age-groups. Psychosocial aspects in people with JH are suggestive of increasing evolution since childhood, also influenced by atypical postural patterns, pain, and inadequate motor performance. Predominant total scores in the upper limbs were suggestive of inability to crawl or crawling differently. Higher total Beighton scores showed a tendency not to crawl, to crawl differently, and a tendency for impaired school performance and delayed ambulation. Most are capable of always sitting in the "concave" position and the "W" position, a condition possible for just under half of the total sample. Both sacrifice hip structures and favor falls. Growing pain" is predominantly located in the lower limbs and occurs in more than one third of the total sample. Lower limb pain since childhood, inadequate motor performance, and JH of the hand with impaired functions contributes to explain the psychosocial implications in this population.